Semi-empirical extrapolation of JET baseline and hybrid scenario fusion performance to D–T operation. (1st November 2021) - Weisen, H.; Sirén, P.; Varje, J.; Kilpeläinen, J.; JET Contributors
Abstract: We present DT neutron rate extrapolations for the baseline and hybrid scenarios of the imminent JET DTE2 experimental campaign using the Monte Carlo heating code ASCOT, using empirically scaled plasmas parameters as inputs. The scalings used are based on the datasets that were produced during scenario development from 2016 to 2020. We find that the target fusion power of 15 MW is likely to be achieved and even surpassed in hybrid scenarios if the same heating power is available as for the best discharges during scenario development. The extrapolated best baseline plasmas are also likely to achieve a fusion power close to that target.